2014
DOI: 10.1021/ic403122j
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Cobalt-Mediated Electrocatalytic CO2Reduction Using a Redox-Active Ligand

Abstract: The cobalt complex [CoIIIN4H(Br)2]+ (N4H = 2,12-dimethyl-3,7,11,17-tetraazabicyclo-[11.3.1]-heptadeca-1(7),2,11,13,15-pentaene) was used for electrocatalytic CO2 reduction in wet MeCN with a glassy carbon working electrode. When water was employed as the proton source (10 M in MeCN), CO was produced (fCO= 45% ± 6.4) near the CoI/0 redox couple for [CoIIIN4H(Br)2]+ (E1/2 = −1.88 V FeCp2+/0) with simultaneous H2 evolution (fH2= 30% ± 7.8). Moreover, we successfully demonstrated that the catalytically active spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
167
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 76 publications
(64 reference statements)
14
167
0
Order By: Relevance
“…These findings are supported by reported X-ray diffraction structures and calculations of similar intermediates for the CO 2 and proton reduction reactions. 52,53 Since the Co(II) species slowly interacts with the ascorbate ion with time, the difference spectra considering a "laser-off" Co(II) square pyramidal with coordinated ascorbate ([LCo(Asc)] + ) are also shown in Figure S10. 3 ] 2+ /Asc, corresponding to the formation and decay of the Co(III) photo-induced species (red dots) with the corresponding kinetics fitting (black solid line).…”
Section: ·3-interaction Of Co(ii) Species With Ascorbate Electron Donormentioning
confidence: 99%
“…These findings are supported by reported X-ray diffraction structures and calculations of similar intermediates for the CO 2 and proton reduction reactions. 52,53 Since the Co(II) species slowly interacts with the ascorbate ion with time, the difference spectra considering a "laser-off" Co(II) square pyramidal with coordinated ascorbate ([LCo(Asc)] + ) are also shown in Figure S10. 3 ] 2+ /Asc, corresponding to the formation and decay of the Co(III) photo-induced species (red dots) with the corresponding kinetics fitting (black solid line).…”
Section: ·3-interaction Of Co(ii) Species With Ascorbate Electron Donormentioning
confidence: 99%
“…A case in point features ligand-centered protonation and subsequent hydride-like reactivity of a nascent C-H bond in a nickel phlorin system (16), although a nickel hydride was not implicated in the cycle for hydrogen evolution. In other work of note, Hull et al (17) reported dehydrogenation of HCO 2 H promoted by proton-responsive hydroxybipyridine-ligated catalysts, and Lacy et al (18) showed that ligand-centered protonation of a cobalt complex could lead to hydrogen evolution.…”
mentioning
confidence: 99%
“…Although various molecular catalysts (porphyrins, corroles, cyclams, naphthyridines, and so forth) with metal centers such as Pd, Ru, Fe, Co, and Ni were investigated,31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 in the years after the discovery of Lehn's catalyst, most research has been focused on Re‐containing complexes. With an estimated average concentration of 1 ppb, Re, together with other noble metals, is one of the rarest elements in Earth's crust.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 99%